Implementation of Video as a Learning Media in Islamic Religious Education and Character Subjects at Unior High School 1 Padang Ganting - Silvia Nilis; Romi Maimori; Abhanda Amra; Susi Herawati (JEICI - Journal of Education and Islamic Contemporary Issue, 2025)
This research is motivated by the implementation of video-based learning media in Islamic Religious Education and Character Education at the Technical Implementation Unit of SMPN 1 Padang Ganting, which has been implemented by Islamic Religious Education and Character Education teachers. This video-based learning has been included in the school's strategic plan, namely a digitalized school that has implemented the independent curriculum since the 2022/2025 academic year. This type of research is field research using descriptive qualitative methods. Data collection techniques include observation, interviews, and documentation. Data processing is carried out descriptively and then described based on the problems that occur in the field using effective sentences. Data sources in this study are primary and secondary. Primary data sources were obtained from the Islamic Religious Education and Character Education teacher, the Principal, and five students. Meanwhile, documentation is obtained in the form of documents related to general findings. Based on research conducted, in planning the implementation of video-based learning media, teachers conduct an initial assessment or diagnostic to determine students' needs and learning styles. Then, they adjust to CP and TP as well as existing learning resources and materials. In the learning process, teachers show videos at the beginning and middle of the learning steps. Teachers often use PBL strategies and combine lecture methods, questions and answers, and discussions so that students can focus and be actively involved in learning.